2015
DOI: 10.1111/josh.12305
|View full text |Cite
|
Sign up to set email alerts
|

A Whole School Approach: Collaborative Development of School Health Policies, Processes, and Practices

Abstract: BACKGROUNDThe Whole School, Whole Community, Whole Child (WSCC) model shows the interrelationship between health and learning and the potential for improving educational outcomes by improving health outcomes. However, current descriptions do not explain how to implement the model.METHODSThe existing literature, including scientific articles, programmatic guidance, and publications by national agencies and organizations, was reviewed and synthesized to describe an overview of interrelatedness of learning and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 8 publications
2
49
0
1
Order By: Relevance
“…In Y2, schools with principals or vice‐principals as the main contact for the COMPASS study were less likely to participate in knowledge brokering. This is particularly interesting given the critical role of administrators in the implementation of school health initiatives . Hence, it emphasizes the importance of developing strategies to engage administrators in knowledge brokering to enhance school outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Y2, schools with principals or vice‐principals as the main contact for the COMPASS study were less likely to participate in knowledge brokering. This is particularly interesting given the critical role of administrators in the implementation of school health initiatives . Hence, it emphasizes the importance of developing strategies to engage administrators in knowledge brokering to enhance school outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly interesting given the critical role of administrators in the implementation of school health initiatives. [42][43][44][45] Hence, it emphasizes the importance of developing strategies to engage administrators in knowledge brokering to enhance school outcomes. However, there was no relationship between a change in school contact or school principal and knowledge brokering participation.…”
Section: Analysis Of Variance (Yr2-3) Pmentioning
confidence: 99%
“…Research in the areas of teaching HIV prevention, vaccinations and the HPV virus has suggested that ongoing training in current health topics is necessary to ensure qualified, experienced health teachers. As Hunt et al notes, qualified, trained health education teachers help students acquire the knowledge, attitudes, and skills necessary for making health‐promoting decisions, achieving health literacy, and adopting health‐enhancing behaviors. Having teachers with a focus on health education also allows schools to leverage the single state‐provided support found to be significantly associated with the outcome in this study, namely health educator professional development in the areas of emotional behavior health and suicide prevention.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…Furthermore, the collaboration of multiple school staff can help to advance health and academic outcomes. 29 A consensus document developed by the Asthma and School subcommittee of the National Heart, Lung, and Blood Institute’s National Asthma Education and Prevention Program stressed the importance of asthma education for all school staff as integral to the establishment of a successful school asthma management program (www.nhlbi.nih.gov/health-pro/resources/lung/managing-asthma-guide-schools-2014-edition-html). In addition to asthma basics education, this resource also contains comprehensive information about the roles that each school staff member can play in a school asthma program, as well as ideas on action items for various staff members that are briefly covered in this white paper.…”
Section: Componentmentioning
confidence: 99%